PREVALENCE OF CESARIAN DELIVERY AND ASSOCIATED FACTORS AMONG MOTHERS WHO GAVE BIRTH AT PUBLIC HOSPITALS IN ETHIOPIA: A CROSS-SECTIONAL STUDY - Yusuf, Abdulahi Mohamud; Sheik, Abdifetah Abdulahi; Ali, Mohamud Hussein; Hassen, Hussen Abdi (Fakultas Ilmu Kesehatan, Kedokteran dan Ilmu Alam (FIKKIA), Universitas Airlangga, 2024)
Background: Caesarean delivery is a procedure used to save a mother’s and foetus’s lives when the labour situation becomes complicated. However, a wrong decision can substantially increase the rates of morbidity and mortality of the woman and the fetus. Purpose: the study aimed to assess the prevalence of cesarean delivery and associated factors. Methods: A health facility-based cross-sectional study has been conducted. A systematic random sampling technique was used. A face-to-face interview was employed to collect data through a pre-tested and structured questionnaire. Descriptive statistics were counted on. A binary logistic regression was employed to assess factors associated with cesarean delivery. The odds ratio and corresponding 95% confidence interval 95% confidence intervals were used. Results: The prevalence of cesarean delivery in this study is 27.4% (95% CI 23.3, 31.8%). monthly income 3,000-6,000 birr [AOR = 3.91 (95% CI: 1.50, 10.17)], previous cesarean delivery [AOR = 15.86 (95% CI: 8.01, 31.40)] and mother not directed counselling [AOR = 2.87 (95% CI: 1.46, 5.68)] are factors significantly associated. The prevalence of cesarean delivery uses is high. Conclusion: The obstetric factors occurring around delivery are the master ground leading cesarean delivery rather than the background characteristics. There is a low rate of pregnant mother counselling. We recommend interventions for the prevention of unnecessary primary cesarean delivery, counselling for pregnant mothers, particular emphasis on training all health care providers, and further investigation.